Isolation of 16 Microsatellite Markers for Spiraea alpina and S. mongolica (Rosaceae) of the Qinghai–Tibet Plateau - Gulzar Khan; Faqi Zhang; Qingbo Gao; Xiujie Jiao; Pengcheng Fu; Rui Xing; Jinhua Zhang; Shilong Chen (Applications in Plant Sciences, 2014)
Premise of the study: A set of microsatellite markers were developed to characterize the level of genetic diversity and gene flow in two plant species endemic to the Qinghai–Tibet Plateau, Spiraea alpina and S. mongolica. Methods and Results: Using the Fast Isolation by AFLP of Sequences Containing repeats (FIASCO) method, 16 microsatellite loci showed polymorphisms in both species. In two populations of each species, the number of alleles per locus ranged from three to 18 in S. alpina and from four to 30 in S. mongolica. Conclusions: These microsatellite markers provide an efficient tool for population genetic studies and will be used to assess the genetic diversity and spatial genetic structure of S. alpina and S. mongolica.